SAT0351 Tocilizumab in Giant Cell Arteritis: A Multicentre Open-Label Study OF34 Patients. (15th July 2016) - Regent, A.; Redeker, S.; Deroux, A.; Kieffer, P.; Ly, K.; Dougados, M.; Eric, L.; Larroche, C.; Guillevin, L.; Bouillet, L.; Espitia, O.; Costedoat-Chalumeau, N.; et al.
Abstract : Background: Giant cell arteritis (GCA) is a vasculitis of large and medium sized arteries affecting people older than 50 years. Glucocorticosteroids (GC) are the mainstay of therapy but relapses are common, resulting in prolonged treatment course and adverse events. IL-6 correlates with disease activity of GCA and temporal artery biopsy samples show enhanced IL-6 production. Cases series and open label studies reported the efficacy of tocilizumab (TCZ) on symptoms and inflamamtory markers in GCA. Objectives: To report the French experience on the efficacy and safety of TCZ in patients with GCA and the evolution after treatment withdrawal. Methods: A retrospective multicenter study on patients treated with TCZ for their GCA was conducted. Treatment efficacy was evaluated at a clinical and biological level. Side effects and evolution after treatment withdrawal were also recorded. Results: Thirty-four patients (27 women and 7 males) aged 70.5±8.2 (mean±SD) were included. Diagnosis of GCA was based on the ACR criteria (30 patients) and/or on imaging abnormalities suggestive of GCA (8 patients). Giant cell disease was treated by GC and another immunosuppressant was added before TCZ introduction in 20/34 patients. Tocilizumab (8 mg/kg monthly) was introduced after a mean disease evolution of 18 months (0–107). It was efficient in all but 6 patients who still had mild symptoms while CRP was reduced from 40.4 mg/L to 1.5 mg/L (p<0, 0001) and GC were tapered from 26.3 to 10.3 mg/day (p<0.0001). One patient died from a septic shock and 3 patients had to stop TCZ for adverse events. Among the 23 patients who stopped treatment (planned medical decision in 20 cases and side effects in 3 cases) eight patients experienced relapses that occurred after a mean of 3.5±1.3 months. Conclusions: TCZ therapy leads to rapid and maintained improvement in patients with refractory GCA. However, side effects should be kept in mind in this population. Questions remain regarding the suspensive nature of this treatment and this should be specifically studied in future studies. Disclosure of Interest: None declared